Replication defective viral genomes exploit a cellular pro-survival mechanism to establish paramyxovirus persistence - Jie Xu; Yan Sun; Yize Li; Gordon Ruthel; Susan R. Weiss; Arjun Raj; Daniel Beiting; Carolina B. López (Nature Communications, 2017)
Replication defective viral genomes (DVGs) can facilitate persistence of paramyxoviruses, but the underlying mechanisms are unclear. Using FISH, Xu et al. here analyze the cellular response to DVGs on a single cell level and show that a MAVS-mediated TNF response specifically extends survival of cells enriched in DVGs.